Defining a stable water isotope framework for isotope hydrology application in a large trans-boundary watershed (Russian Federation/Ukraine) - Vystavna, Yuliya; Diadin, Dmytro; Huneau, Frédéric (Isotopes in environmental and health studies, 2018)
Stable isotopes of hydrogen (2H) and oxygen (18O) of the water molecule were used to assess the relationship between precipitation, surface water and groundwater in a large Russia/Ukraine trans-boundary river basin. Precipitation was sampled from November 2013 to February 2015, and surface water and groundwater were sampled during high and low flow in 2014. A local meteoric water line was defined for the Ukrainian part of the basin. The isotopic seasonality in precipitation was evident with depletion in heavy isotopes in November-March and an enrichment in April-October, indicating continental and temperature effects. Surface water was enriched in stable water isotopes from upstream to downstream sites due to progressive evaporation. Stable water isotopes in groundwater indicated that recharge occurs mainly during winter and spring. A one-year data set is probably not sufficient to report the seasonality of groundwater recharge, but this survey can be used to identify the stable water isotopes framework in a weakly gauged basin for further hydrological and geochemical studies.
Keywords: hydrogen-2; deuterium; Hydrology; hydrologie; Seasons; isotope hydrology; monitorování životního prostředí; Ukrajina; podzemní voda; Deuterium; Rivers; surface water; oxygen-18; Ukraine; roční období; hydrological processes; Oxygen Isotopes; izotopy kyslíku; Groundwater; řeky; Russia; Environmental Monitoring; precipitation; Russian Federation; Rusko